Project Management in the Manufacturing Sector - Gujar, Shubham Mohan; Shafighi, Najla (Archives of Business Research, 2023)
This study will analyze the role of automation cloud-based project management software in managing and optimizing manufacturing plans and data. The objective is to understand the evolution of automated and cloud-based project management software like Jira and Asana by incorporating beneficial of traditional Gantt charts and work breakdown structures for manufacturing companies. The questionnaire was designed to collect data from 100 project managers employed in various manufacturing units. The data were quantitatively analyzed using both statistical analysis and a test of association. The objective was to understand the factors contributing to the automated and cloud-based project management software, and the challenges faced by the project managers in the incorporation of traditional Gantt charts and work breakdown structures, in the complex and time-consuming tasks associated with project management.